2017
DOI: 10.2147/clep.s127695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glomerular filtration rate at dialysis initiation on survival in patients with advanced chronic kidney disease: what is the effect of lead-time bias?

Abstract: PurposeCurrent clinical guidelines recommend to initiate dialysis in the presence of symptoms or signs attributable to kidney failure, often with a glomerular filtration rate (GFR) of 5–10 mL/min/1.73 m2. Little evidence exists about the optimal kidney function to start dialysis. Thus far, most observational studies have been limited by lead-time bias. Only a few studies have accounted for lead-time bias, and showed contradictory results. We examined the effect of GFR at dialysis initiation on survival in chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 42 publications
(62 reference statements)
0
25
0
1
Order By: Relevance
“…Despite extensive previous literature, evidence on whether an optimal glomerular filtration rate to start dialysis exists, and if so where it lies, is lacking. Previous observational studies that attempted to investigate multiple estimated glomerular filtration rate (eGFR) strategies have been limited by insufficient power, 11 12 13 immortal time bias, 14 15 16 17 or lead time and selection biases. 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 In 2010 the Initiating Dialysis Early and Late (IDEAL) trial showed that a strategy to start dialysis at an eGFR of 10-14 mL/min/1.73 m 2 was not superior to one of waiting until symptoms develop or eGFR is 5-7 mL/min/1.73 m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive previous literature, evidence on whether an optimal glomerular filtration rate to start dialysis exists, and if so where it lies, is lacking. Previous observational studies that attempted to investigate multiple estimated glomerular filtration rate (eGFR) strategies have been limited by insufficient power, 11 12 13 immortal time bias, 14 15 16 17 or lead time and selection biases. 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 In 2010 the Initiating Dialysis Early and Late (IDEAL) trial showed that a strategy to start dialysis at an eGFR of 10-14 mL/min/1.73 m 2 was not superior to one of waiting until symptoms develop or eGFR is 5-7 mL/min/1.73 m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Однако, они оказались противоречивыми: большие относительные риски смерти были связаны с большей измеренной СКФ, но с меньшей расчетной СКФ [5]. Анализ исследования NECOSAD продемонстрировал различный эффект коррекции по предвзятости пре-ждевременного старта для измеренной СКФ в срав-нении с расчетной СКФ, при этом в исследовании присут ствовало серьезное ограничение: пациенты, лечившиеся на диализном катетере, были исключены из исследования (а это возможный маркер экстренного старта) [25]. В другом анализе того же регистра пред-диализное снижение измеренного, но нерасчетного СКФ было фактором риска смерти на диализе [26].…”
Section: Discussionunclassified
“…In nephrology, it has become widely known as a problem of cohort studies comparing policies of early and late start of dialysis. When patients start dialysis at a higher eGFR without severe uraemic signs and symptoms, and their survival is compared to those starting dialysis at a lower eGFR with severe uraemic signs and symptoms, then this comparison may suffer from lead‐time bias favouring those with an early start . Some studies have attempted to take lead‐time bias into account by estimating the date at which patients had a predefined level of eGFR before dialysis start and then counting survival time in both early and late starters from that date onwards …”
Section: Information Biasmentioning
confidence: 99%